دراسة قياسية لمحددات سعر الصرف الحقيقي (الدينار الجزائري نموذجا 2000-2014) - بنين, بغداد; براق, محمد (جامعة الوادي - University of Eloued, 2016)
تتمحور هذه الورقة حول إمكانية إيجاد محددات رئيسية لسعر الصرف الحقيقي استنادا إلى النظريات الاقتصادية، في هذا الإطار يمكننا صياغة نموذج قياسي عام بناءا لما توفر لنا من معطيات إحصائية واقتصادية، واختيار أحسن نموذج ممكن استخدامه لأغراض تحليل السياسة الاقتصادية وكذا يمكن للحاجة التنبؤ باتجاهات أسعار الصرف المستقبلية. Centered this paper about the possibility of a major determinants of the exchange rate on the basis of economic theories, in this context, we can formulate a standard model year based to provide us with the statistical and economic data, and choose the best possible model used for the purposes of economic policy analysis as well as can be to the need to predict trends in exchange rates and future.
مقال
Keywords: سعر الصرف،انظمة سعر الصرف، طريقة الانحدار الخطي (OLS).